Resistência à Síndrome Ascítica, Competência Homeotérmica e Níveis de Hsp70 no Coração e Pulmão de Frangos de Corte - Hernandes, Renata; Ferro, Jesus Aparecido; Gonzales, Elisabeth [UNESP]; Macari, Marcos [UNESP]; Bernal, Francisco Ernesto Moreno; Ferro, Maria Inês Tiraboschi (Sociedade Brasileira de Zootecnia, 2002)
Como em outros seres vivos, também nas células das aves ocorre a síntese das proteínas de baixo peso molecular (Hsp), cujo aumento é induzido sob condições de estresse. As Hsps têm um papel importante na manutenção da integridade celular, questiona-se o seu envolvimento no mecanismo de proteção celular de órgãos alvos na ocorrência da síndrome ascítica (SA). Este trabalho objetivou avaliar a temperatura corporal e os níveis da Hsp70 no coração e pulmão de frangos de corte Hubbard (sensível à SA) e caipira de pescoço-pelado (resistente), criados em termoneutralidade (25°C) e frio (16°C) entre 10 e 45 dias de idade. Foram utilizados 192 pintos machos, 96 de cada linhagem. Não houve mortalidade por SA nas aves caipiras. Nas aves Hubbard, a mortalidade devida à SA foi de 4% e 41% em ambiente termoneutro e frio, respectivamente. em ambiente frio, a temperatura corporal das aves Hubbard foi menor que a das caipiras. A temperatura corporal e o nível de Hsp70 do coração das aves Hubbard diminuíram com o aumento da idade, mas não nas aves caipiras, os quais se mantiveram constantes, inclusive a Hsp70 do pulmão. Independente da idade ou da temperatura, o nível de Hsp70 no pulmão das aves caipiras era superior ao das aves Hubbard. em relação às aves Hubbard, as caipiras são homeotérmicas mais competentes e apresentam uma maior indução de Hsp70 nos órgãos primariamente afetados na SA, mas este não parece ser o sistema de proteção contra SA, a qual as aves de pescoço pelado são resistentes.

Similar to other living animals, the cells of the birds also synthesize small proteins (heat shock protein, Hsp), which increasing levels can be induce by stress. The Hsp have a relevant function in maintaining the integrity of the cell, and we question if they are involved in the mechanism of the cellular protection of target organs affected by ascites syndrome (AS). The objective of this study was to evaluate the body temperature, and the Hsp70 levels in the heart and lungs of broilers Hubbard (sensitive to AS) and naked-neck (resistant), raised under thermo-neutral (25C) or cold (16C) environments between 10 and 45 days of raising. We used 192 male chicks, 96 from each broiler strain. No AS mortality occurred among naked-neck birds, but 4% and 41% of Hubbard broilers submitted, respectively, to thermo-neutral and cold temperatures died due to AS. The body temperatures of cold-exposed-Hubbard-birds were lowers than that of naked-necks. The Hsp70 levels of heart and the body temperature of Hubbard chicks decreased as the age increased, for naked-neck these variables were constant during their lives, including the Hsp70 level in the lung cells. Independently from age or temperature effects, the lung cells of naked-neck birds had higher Hsp70 levels than those of Hubbard chickens. Comparing to Hubbard broilers, the naked-neck birds are more competent homoeothermics, and present superior level of Hsp70 in the organs firstly affected by AS, but it did not seem the system of protection against AS, in which the naked-neck birds are resistant.
Resistance to Ascites Syndrome, Homoeothermic Competence and Levels of Hsp70 in the Heart and Lung of Broilers
Keywords: frango de corte; Hsp70; linhagem; síndrome ascítica; tolerância térmica; ascites syndrome; broilers; thermo-tolerance; Hsp70; strain